Faktor-Faktor Penyebab Stunting Pada Anak Balita Di Desa Lamahang dan Desa Wasbakat Kabupaten Buru - Buamona, Ritzi I; Moniharapon, Erynola; Mailoa, Meitycorfrida (Jurnal Agrosilvopasture-Tech, 2024)
Stunting is a condition of poor nutrition in toddlers, which causes stunted physical growth, so the child is too short compared to normal toddler standards. This research aims to determine the factors influencing stunting in Lamahang Village and Wasbakat Village, Buru Regency. The population in the study was 121 toddlers. The samples were 60 toddlers from each village using a purposive sampling technique. This research method is an interview using a questionnaire. The relationship between factors influencing stunting was analyzed using the Spearman rank correlation test. The research results show that stunting is related to stunting, such as the number of children, family income, consumption of diverse foods, drinking water sources, latrines, and habitable houses. At the same time, maternal education and age at marriage have no relationship to stunting in Lamahang Village. Meanwhile, in Wasbakat Village, factors related to stunting are family income, consumption of various foods, drinking water sources, latrines, and livable houses. Maternal education, number of children, and age at marriage have no relationship with stunting in Wasbakat Village.